Trading caterpillar fungus in Tibet : when economic boom hits rural area - Sulek, Emilia Roza (Amsterdam : Amsterdam University Press, 2019)
When the demand for, and prices of caterpillar fungus (Ophiocordyceps sinensis, 'the Himalayan Viagra', long a part of traditional Chinese medicine) soared, the pastoralists of Golok on the Tibetan plateau where the fungus is endemic dug up, dried and sold the fungus to traders. In the process, these yak and sheep farmers, used to living on the edge of subsistence, became wealthy beyond their imagination. Trading Caterpillar Fungus in Tibet: When Economic Boom Hits Rural Area tells the story of what they do with the money they earned from gathering and trading caterpillar fungus, and what this money does to them, revealing a sophistication few outsiders would credit them for.
Title from publisher's bibliographic system (viewed on 20 Nov 2020).
Keywords: Tibet Autonomous Region (China) -- Economic conditions; Tibet, Plateau of -- Economic conditions; Farmers -- Tibet, Plateau of